Tareas escolares y participación de los padres en modalidad de enseñanza remota en niños de la Institución Educativa Inicial N° 847 Nuestra Señora de la Purísima Punchana 2021 - Aguilar Peixoto, Clausia Diana (2022)
The present research was carried out in order to determine the relationship between school tasks and parental participation in remote teaching modality in children of the Initial Educational Institution No. 847 Nuestra Señora de la Purísima of the district of Punchana in 2021. The type of research considered is relational, with a field, cross-sectional, and bivariate design. For the study, 115 parents of primary school children were considered, and the sample has been census, which is to say, the 115 parents. The survey was the technique and two questionnaires as instruments to collect the data, these were validated through the judgment of judges. The conclusion of the research is that 73.9% of parents who show a high level of participation have children in high compliance with the school tasks assigned in the educational institution.